Til genitivapostroffen’s forsvar - Juul Nielsen, Peter (Danske Studier, 2024)
The use of apostrophe before the genitive s in Danish in e.g. Poul’s pølser ‘Poul’s sausages’ is a pet aversion among many of those concerned about correct language, and indeed the apostrophe in Poul’s pølser is a violation of the current Danish spelling rules. This article presents arguments in defence of a general use of ’s as the marker of the genitive in Danish. The point of departure is an account of the grammar of the genitive in Modern Danish and the status of the element s, which is not in the present-day language an inflectional ending on the word level, but a clitic on the level of the noun phrase. Having established the structural properties of the genitive, the article discusses the primary principles of language regulation and spelling conventions that speak in favour of the genitive apostrophe and against it. The article concludes that there are substantial and quite compelling arguments in favour of approving ’s as a general genitive marker based on internal linguistic properties and a democratic approach to language regulation.